"More of a Kind of Patchy Transition into University as Opposed to the Kind of Smooth Story that People Expect." Transitions to Higher Education for Care-Experienced Students - Bayfield, Hannah (International Journal of Educational and Life Transitions, 2023)
Despite an increased focus on supporting under-represented groups into Higher Education (HE), care-experienced young people are still significantly less likely to transition into HE than their peers who have not had this experience. With rates of children taken into care increasing in Wales, there is value in understanding how best to support care-experienced young people with educational transitions. Based on pan-Wales research into access to, and success in, HE for care-experienced young people, this paper presents the experiences of 13 young people in Wales regarding educational transitions and the support they have – or have not – had in their transitions to university. Recommendations are made for improving transition support and for creating better signposting to existing support.